Antifungal Effect of Probiotic Lactobacillus casei on Drug-Resistant Oral Candida albicans Isolated from Patients with Hematological Malignancy: An In vitro Study - Seyedeh Saba Sharifzadeh; Ensieh Lotfali; Simin Lesan; Taraneh Farrokhnia (Shiraz University of Medical Sciences, 2023)
Statement of the Problem: Candida albicans (C. albicans) is recognized as the most common opportunistic pathogen in patients with an impaired immune system, and due to the frequent use of antifungal medicine, a variety of drug-resistant species are developing. Probiotics are a part of the human microbiome and natural competitors of Candida by producing lactic acid, low pH, and other secreted metabolites. The role of probiotics in preventing fungal infections has always been discussed.Purpose: This study aimed to investigate the antifungal effect of Lactobacillus casei (L. casei) on fluconazole- and amphotericin B-resistant C. albicans species isolated from the oral cavity of acute myeloid leukemia patients.Materials and Method: In this experimental study, eight strains of fluconazole- and amphotericin B-resistant C. albicans were used. The antifungal effects of probiotic L. casei and nystatin were measured by the co-aggregation method 1, 2, and 4 h after beginning the study. After each hour of exposure, C. albicans and L. casei colonies were counted.Results: L. casei had a significant ability to aggregate with both fluconazole- and amphotericin B-resistant C. albicans in all designated intervals, which increased with time. In the first hour of the study, no significant difference was observed between the effects of L. casei on the two drug-resistant strains. However, as time passed, it had a more significant antifungal effect on fluconazole, compared to amphotericin B resistant species (p Value<0.001). Cell counts showed that the number of fungal cells decreased significantly as time passed (p< 0.001).Conclusion: L. casei had a significant ability to aggregate with both drug-resistant C. albicans species and showed higher antifungal activity on fluconazole-resistant than amphotericin B-resistant species.